A fluorine-containing liquid crystal polyester with high thermal conductivity and low dielectric constant and its preparation method and application

By introducing fluorine atoms into the liquid crystal polyester, liquid crystal polyester with high thermal conductivity and low dielectric constant is prepared through polycondensation reaction, which solves the problems of heat accumulation and high dielectric constant of electronic components, and achieves efficient thermal conductivity and signal transmission.

CN116496482BActive Publication Date: 2025-01-10GUANGZHOU CHEM CO LTD CHINESE ACADEMY OF SCI +3
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310356985.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-06
Publication Date
2025-01-10
Estimated Expiration
2043-04-06

AI Technical Summary

Technical Problem

During the high frequency, miniaturization and high integration of electronic components, the temperature increases due to heat accumulation, shortens service life, and high dielectric constants in high-frequency circuits hinder signal transmission, making it difficult for existing materials to take into account high thermal conductivity and low dielectricity. constant.

Method used

By polycondensing the diol and fluorine-containing dicarboxylic acid in the presence of a catalyst, a fluorine-containing liquid crystal polyester is prepared, and the dielectric constant of fluorine atoms are used to reduce the dielectric constant and improve the thermal conductivity.

Benefits of technology

The liquid crystal polyester material with high thermal conductivity and low dielectric constant is achieved, which improves the thermal conductivity and thermal stability of the material, while reducing dielectric loss, and is suitable for heat dissipation materials for electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116496482B_ABST
    Figure CN116496482B_ABST
Patent Text Reader

Abstract

The present invention provides a fluorine-containing liquid crystal polyester with high thermal conductivity and low dielectric constant. The method is to gradually condense a diol monomer and a fluorine-containing dibasic acid in an equal molar ratio under the condition of countless zinc acetate and antimony trioxide as catalysts. Finally, the condensation is performed by hot pressing or evaporating solvents. The thermal conductivity of the high thermal conductivity and low dielectric constant liquid crystal polyester prepared by the present invention can reach 0.425W m ‑1 K ‑1 , at a frequency of 10 MHz, the dielectric constant is 2.97. The thickness is 0.1 to 2.5 mm, and products with various thicknesses, different thermal conductivities and dielectric constants can be prepared, suitable for mobile phones, tablet computers and various electronic products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of fluorine-containing liquid crystal polyesters, and particularly relates to a fluorine-containing liquid crystal polyester with high thermal conductivity and low dielectric constant, and a preparation method and application thereof. Background Art

[0002] The progress of science and technology has led to the high frequency, miniaturization and high integration of electronic components, resulting in a large amount of heat accumulation in the unit volume of electronic components, which has caused the temperature of electronic components to rise, shortened the service life, reduced the performance and reliability of the entire system, and had a huge impact on the user experience. Therefore, efficient heat conduction and heat dissipation have become key issues in the field of thermal management. Effective heat dissipation devices or materials are needed to dissipate the internal heat of the device in time to ensure the normal use of electronic devices. At the same time, with the rapid development of electronic information technology, the integration of electronic products has been continuously improved, and the speed and frequency have also become higher and higher; in high-frequency circuits, the transmission speed of signals can be expressed as: V∝c / √ε, where V-signal transmission rate, C-speed of light in vacuum, ε-dielectric constant of substrate. It can be seen that when polymers are used as output end components of electronic products, the lower the dielectric constant, the more conducive to signal transmission. At the same time, with the development of mobile communication technology and the trend of high frequency, high integration and miniaturization of electronic devices, the local heat accumulation will seriously affect the operation safety of precision devices and shorten the service life, so materials with high thermal conductivity, low dielectric constant and low dielectric loss are now the research hotspots. Thermotropic liquid crystal polyester has excellent melt fluidity, heat resistance, strength and rigidity, and is particularly suitable for making thin-walled, complex-structured products using surface mounting technology. Therefore, it is widely used as electronic and electrical components and optical parts. Summary of the invention

[0003] The purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and provide a fluorine-containing liquid crystal polyester with high thermal conductivity and low dielectric constant.

[0004] Another object of the present invention is to provide a method for preparing the above-mentioned fluorine-containing liquid crystal polyester with high thermal conductivity and low dielectric constant.

[0005] Another object of the present invention is to provide an application of the above-mentioned fluorine-containing liquid crystal polyester with high thermal conductivity and low dielectric constant.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] A fluorine-containing liquid crystal polyester with high thermal conductivity and low dielectric constant, wherein the structural formula is at least one of the following:

[0008]

[0009] Formula (1);

[0010]

[0011] Formula (2);

[0012]

[0013] Formula (3);

[0014]

[0015] Formula (4).

[0016] The method for preparing the above-mentioned fluorine-containing liquid crystal polyester with high thermal conductivity and low dielectric constant comprises the following steps:

[0017] The diol and the fluorine-containing dicarboxylic acid are mixed, a catalyst is added, and a condensation polymerization reaction is carried out by heating. Then, the heating reaction is continued while filtering to obtain a fluorine-containing liquid crystal polyester with high thermal conductivity and low dielectric constant.

[0018] The diol is at least one of 1,4-benzenedimethanol and biphenyl diol.

[0019] The fluorine-containing dicarboxylic acid is at least one of 3-fluorophthalic acid, 4,5-difluorophthalic acid and tetrafluorophthalic acid.

[0020] The molar ratio of the diol to the fluorine-containing dicarboxylic acid is 1-2:1-2, preferably 1:1.

[0021] The catalyst is anhydrous zinc acetate and antimony trioxide.

[0022] The mass of the anhydrous zinc acetate is 0.1-0.3% of the total mass of the reaction system, preferably 0.2%.

[0023] The mass of the antimony trioxide is 0.2-0.4% of the total mass of the reaction system, preferably 0.3%.

[0024] The conditions for the heating polycondensation reaction are 150-170° C. for 2-4 hours, preferably 160° C. for 3 hours.

[0025] The condition of the filtration is that the vacuum degree is lower than 30Pa.

[0026] The conditions for the continued heating reaction are to react at 150-170° C. for 2-4 hours; preferably, to react at 170° C. for 3 hours.

[0027] The preparation method of biphenyl dihydric alcohol comprises the following steps:

[0028] The halogenated alcohol, biphenyl diphenol and anhydrous potassium carbonate are refluxed for reaction under a protective atmosphere, and after cooling, water is added, filtered, neutralized, washed with water and dried to obtain biphenyl dihexanol.

[0029] The halogenated alcohol is at least one of 2-bromoethanol, 3-chloro-1-propanol, 4-chlorobutanol or 6-chlorohexanol.

[0030] The molar ratio of the halogenated alcohol to biphenol is 2-4:1, preferably 3:1.

[0031] The protective atmosphere is a nitrogen atmosphere.

[0032] The reflux reaction conditions are condensation reflux for 20 to 30 hours, preferably condensation reflux for 24 hours.

[0033] The cooling is cooling to room temperature.

[0034] The neutralization is to add hydrochloric acid to adjust the pH to 1.

[0035] The drying conditions are 70-90° C. for 20-30 hours, preferably 80° C. for 24 hours.

[0036] The above-mentioned high thermal conductivity and low dielectric constant fluorinated liquid crystal polyester is used in the preparation of electronic devices.

[0037] The above-mentioned high thermal conductivity and low dielectric constant fluorinated liquid crystal polyester is used as a heat dissipation material for electronic devices.

[0038] Compared with the prior art, the present invention has the following advantages and effects:

[0039] (1) The biphenyl diol prepared by the present invention contains liquid crystal primitives, and after polycondensation with a dibasic acid, it becomes a thermotropic liquid crystal. Through observation under a polarizing microscope, an obvious liquid crystal phase can be observed between the melting point and the clearing point. The orientation arrangement of the liquid crystal makes the chain structure more regular, reduces phonon scattering, and improves its thermal conductivity.

[0040] (2) The present invention introduces fluorine into the liquid crystal polyester by polycondensation of fluorine-containing dicarboxylic acid and biphenyl diol, thereby reducing the polarizability of the material and effectively reducing the dielectric constant and dielectric loss.

[0041] (3) The high thermal conductivity and low dielectric constant liquid crystal polyester prepared by the present invention has a simple preparation process. The orientation arrangement of the liquid crystal reduces phonon scattering. The introduction of fluorine atoms reduces the polarizability of the system and increases the free volume, which effectively reduces the dielectric constant and dielectric loss of the liquid crystal polyester. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 It is the infrared spectrum of the polymer synthesized in Examples 1 to 4.

[0043] Figure 2 These are polarizing microscope photographs of the polymers synthesized in Examples 1 to 4.

[0044] Figure 3 It is the XRD spectrum of the polymer synthesized in Examples 1-4.

[0045] Figure 4 It is the DSC spectrum of the polymer synthesized in Examples 1-4.

[0046] Figure 5 It is the thermogravimetric curve of the polymer synthesized in Examples 1 to 4. DETAILED DESCRIPTION

[0047] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.

[0048] If the specific experimental conditions are not specified in the following embodiments, the conventional experimental conditions or the experimental conditions recommended by the reagent company are usually followed. The materials and reagents used, unless otherwise specified, are all reagents and materials obtained from commercial sources.

[0049] Example 1

[0050] This embodiment provides a method for preparing fluorine-containing polyester.

[0051] 1.38 g of 1,4-benzenedimethanol and 2.38 g of tetrafluorophthalic acid were subjected to polycondensation. The reaction conditions were as follows: 0.0075 g of anhydrous zinc acetate and 0.0113 g of antimony trioxide were added, and the reaction was carried out at 150 degrees Celsius for 3 hours. After slowly heating to 160 degrees Celsius, vacuum filtration was performed, and the vacuum degree of the system was reduced (below 30 Pa) by oil pump filtration. At the same time, water and small molecules in the system were removed to make the polycondensation reaction proceed in the forward direction. After continuing to react at 160 degrees Celsius for 3 hours, the reaction was stopped. The obtained product was shown in formula (1). The product was taken out and hot-pressed.

[0052]

[0053] Formula (1)

[0054] The prepared fluorinated liquid crystal polyester is named polyester 1, and its structural formula is shown in formula (1). Experiments are conducted to test its thermal conductivity, dielectric constant and dielectric loss, and it is characterized and tested using an infrared spectrometer, a polarizing microscope, an XRD diffractometer and a differential scanning calorimeter. The experimental results are as follows: Figures 1 to 5 As shown, the thermal conductivity of polyester 1 is 0.183 W m -1 K -1 , at a frequency of 10 MHz, the dielectric constant is 4.48 and the dielectric loss is 1.89×10 -2 Its infrared spectrum is shown in the attached Figure 1 As shown in the polyester 1, according to the attached Figure 2 It can be seen that the polymer is in an amorphous state and has no crystallinity. Figure 3The wide sealing properties of amorphous polymers are also shown in the attached Figure 4 The melting point of the polymer was shown to be 58.3°C and the temperature of the initial decomposition (thermal weight loss 5%) was only 253.2°C.

[0055] Example 2

[0056] This embodiment provides a method for preparing a liquid crystal polyester.

[0057] (1) 40 ml of 6-chlorohexanol, 18.6 g of biphenyl diphenol and 124 g of anhydrous potassium carbonate were placed in a 250 ml three-necked flask, and condensed and refluxed for 24 h under nitrogen protection. After the reactants were cooled to room temperature, 250 ml of deionized water was added and stirred, and then filtered to remove the solvent. Excess hydrochloric acid was added to make the pH value 1, and the excess potassium carbonate was reacted. After washing with water for several times, the obtained product was dried in a vacuum oven at 80 degrees Celsius for 24 h to obtain biphenyl dihydroxyhexanol;

[0058] (2) 3.54 g of diphenyl dihydric alcohol and 1.66 g of phthalic acid are subjected to condensation polymerization. The reaction conditions are as follows: 0.0104 g of anhydrous zinc acetate and 0.0156 g of antimony trioxide are added, and the reaction is carried out at 180 degrees Celsius for 3 hours. After slowly heating to 190 degrees Celsius, the vacuum degree of the system is reduced (below 30 Pa) by vacuum filtration, and water and small molecules in the system are removed at the same time, so that the condensation polymerization reaction proceeds in the forward direction. After reacting for 3 hours, the reaction is stopped. The obtained product is shown in formula (1). The product is taken out and formed into a film by hot pressing or volatilizing the solvent.

[0059]

[0060] Formula (2)

[0061] The prepared liquid crystal polyester is named polyester 2, and its structural formula is shown in formula (2). It is characterized and tested according to the method of Example 1. The experimental results show that the thermal conductivity of polyester 2 is 0.263 W m -1 K -1 , at a frequency of 10 MHz, the dielectric constant is 4.88 and the dielectric loss is 1.80×10 -2 Its infrared spectrum is shown in the attached Figure 1 The polyester shown in FIG. Figure 2 It can be seen that the polymer has good crystallinity. Figure 3 ) and DSC test (attached Figure 4 ) also shows that the polymer is a liquid crystal polymer, with Figure 4 Its melting point is 62.5° C. and its clearing point is 83.6° C. Its thermal stability is improved compared with that of Example 1, and its initial decomposition temperature (thermal weight loss 5%) is 371.5° C.

[0062] Example 3

[0063] This embodiment provides a method for preparing a liquid crystal polyester with high thermal conductivity and low dielectric constant.

[0064] (1) Prepare diphenyl diol by referring to the method of Example 2;

[0065] (2) 3.54 g of diphenyl dihydric alcohol and 1.84 g of 3-fluorophthalic acid were subjected to condensation polymerization. The reaction conditions were as follows: 0.0108 g of anhydrous zinc acetate and 0.0161 g of antimony trioxide were added, and the reaction was carried out at 180 degrees Celsius for 3 hours. After slowly heating to 190 degrees Celsius, the vacuum degree of the system was reduced (below 30 Pa) by vacuum filtration, and water and small molecules in the system were removed at the same time, so that the condensation polymerization reaction proceeded in the forward direction. After continuing the reaction at 190 degrees Celsius for 3 hours, the reaction was stopped. The obtained product was shown in formula (1). The product was taken out and formed into a film by hot pressing or volatilizing the solvent.

[0066]

[0067] Formula (3)

[0068] The prepared liquid crystal polyester with high thermal conductivity and low dielectric constant is named polyester 3, and its structural formula is shown in formula (3). It is characterized and tested according to the method of Example 1. The experimental results show that the thermal conductivity of polyester 3 is 0.355 W m - 1 K -1 , at a frequency of 10 MHz, the dielectric constant is 3.99 and the dielectric loss is 1.37×10 -2 . The infrared spectrum is attached Figure 1 The polyester in the three shown; according to the attached Figure 2 It can be seen that the polymer has good crystallization properties and Figure 3 and attached Figure 4 It is also shown that the polymer is a liquid crystal polymer. Figure 4 It can be seen that its melting point is 89.8℃ and its clearing point is 109.5℃. Figure 5 The temperature of its initial decomposition (thermal weight loss 5%) is 371.5°C; the above data, compared with the polymer synthesized in Example 2, proves that the introduction of fluorine into the main chain of the liquid crystal polyester improves its thermal conductivity, decreases the dielectric constant, and improves the crystallinity and thermal stability.

[0069] Example 4

[0070] This embodiment provides a method for preparing a liquid crystal polyester with high thermal conductivity and low dielectric constant.

[0071] (1) Prepare diphenyl diol by referring to the method of Example 2;

[0072] (2) 3.54 g of diphenyl dihydric alcohol and 2.38 g of tetrafluorophthalic acid are subjected to a condensation reaction. The reaction conditions are as follows: 0.0118 g of anhydrous zinc acetate and 0.0178 g of antimony trioxide are added, and the reaction is carried out at 180 degrees Celsius for 3 hours. After slowly heating to 190 degrees Celsius, the vacuum degree of the system is reduced (below 30 Pa) by vacuum filtration, and water and small molecules in the system are removed at the same time, so that the condensation reaction proceeds in the forward direction. After continuing the reaction at 190 degrees Celsius for 3 hours, the reaction is stopped. The obtained product is shown in formula (1). The product is taken out and formed into a film by hot pressing or volatilizing the solvent.

[0073]

[0074] Formula (4)

[0075] The prepared high thermal conductivity and low dielectric constant liquid crystal polyester is named polyester 4, and its structural formula is shown in formula (4). It is characterized and tested according to the method of Example 1. The experimental results show that the thermal conductivity of polyester 4 can reach 0.425 W m -1 K -1 At a frequency of 10 MHz, the dielectric constant is 2.97 and the dielectric loss is 8.47×10 -4 , and has good thermal stability, and its performance is better than that of the liquid crystal polyester obtained in Examples 1 to 3.

[0076] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A fluorinated liquid crystal polyester with high thermal conductivity and low dielectric constant, characterized in that The structural formula is at least one of the following: Formula (1); Formula (2); Formula (3); Formula (4).

2. The method for preparing the fluorinated liquid crystal polyester with high thermal conductivity and low dielectric constant according to claim 1, characterized in that The steps include: The diol and the fluorine-containing dicarboxylic acid are mixed, a catalyst is added, and a condensation polymerization reaction is carried out by heating. Then, the heating reaction is continued while filtering to obtain a fluorine-containing liquid crystal polyester with high thermal conductivity and low dielectric constant.

3. The preparation method according to claim 2, characterized in that: The diol is at least one of 1,4-benzenedimethanol or biphenyl diol; The fluorine-containing dicarboxylic acid is at least one of 3-fluorophthalic acid, 4,5-difluorophthalic acid, and tetrafluorophthalic acid; The molar ratio of the diol to the fluorine-containing dicarboxylic acid is 1-2:1-2.

4. The preparation method according to claim 2, characterized in that: The catalyst is anhydrous zinc acetate and antimony trioxide; The mass of the anhydrous zinc acetate is 0.1-0.3% of the total mass of the reaction system; The mass of the antimony trioxide is 0.2-0.4% of the total mass of the reaction system.

5. The preparation method according to claim 2, characterized in that: The conditions of the heating polycondensation reaction are 150 to 170 ° C for 2 to 4h; The filtration condition is that the vacuum degree is lower than 30Pa; The conditions for the continued heating reaction are to react at 150-170° C. for 2-4 hours.

6. The preparation method according to claim 3, characterized in that The preparation method of the biphenyl dihydric alcohol comprises the following steps: The halogenated alcohol, biphenyl diphenol and anhydrous potassium carbonate are refluxed for reaction under a protective atmosphere, and after cooling, water is added, filtered, neutralized, washed with water and dried to obtain biphenyl dihexanol.

7. The preparation method according to claim 6, characterized in that: The halohydrin is at least one of 2-bromoethanol, 3-chloro-1-propanol, 4-chlorobutanol or 6-chlorohexanol; The molar ratio of the halogenated alcohol to the diphenol is 2-4:

1.

8. The preparation method according to claim 6, characterized in that: The protective atmosphere is a nitrogen atmosphere; The reflux reaction conditions are condensation reflux for 20 to 30 hours; The cooling is cooling to room temperature; The neutralization is to add hydrochloric acid to adjust the pH to 1; The drying condition is 70-90° C. for 20-30 hours.

9. Use of the fluorinated liquid crystal polyester with high thermal conductivity and low dielectric constant as claimed in claim 1 in the preparation of electronic devices.

10. Use of the fluorine-containing liquid crystal polyester with high thermal conductivity and low dielectric constant as claimed in claim 1 as a heat dissipation material for electronic devices.

Citation Information

Patent Citations

  • High-fluorine content heat-resistant polyarylether resin and preparation method thereof

    CN106750257A

  • Intrinsic thermoplastic heat conducting polyester material, preparation method and application thereof

    CN110229318A